IMPLEMENTASI PROGRAM STBM SEBAGAI UPAYA PENINGKATAN PENGELOLAAN SAMPAH RUMAH TANGGA DAN KUALITAS AIR BERSIH DI RT 03 KELURAHAN SINDANG SARI, KOTA SAMARINDA TAHUN 2025 - Rusdi Rusdi; Muhammad Habibi; Shaila Fadiliana Sari; Fitriyani Fitriyani; Moh. Aldy Nurrahman; Muh. Resky; Rian Rizki Ramadhani; Dita Anita Putri (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Samarinda's rapid population growth is not matched by the readiness of sanitation infrastructure, causing residents of RT 03, Sindang Sari Village, to consume murky water and openly burn waste, which poses a risk to respiratory health. The focus of this research problem is to optimize household waste management and water quality through the implementation of the Community-Based Total Sanitation (STBM) program. Key stages of the research include situational analysis using the USG method, providing education on waste sorting, training in making eco-enzymes from organic waste, and installing simple water filter technology for sixty selected respondents. The quantitative research findings show a significant increase in residents' understanding from a pre-test score range of 60–100 to 90–100 in the post-test stage. Although the Wilcoxon test results yielded a statistically significant value of 0.102, which does not indicate a significant difference due to the already high initial score, descriptively there has been a real change in behavior in the form of a reduction in the practice of burning waste and an increase in the ability to purify water independently. The main conclusion of this study confirms that the participatory intervention strategy through STBM is very effective in building community independence in maintaining environmental hygiene. This initiative has successfully transformed old habits into sustainable clean living patterns to improve the quality of life and public health through a beautiful and safe residential environment for the future of all residents in the area as a whole and integrated.